The effectiveness of BARUSIDA application on arabic learning outcomes of students at junior high school - Qolami, Hawa; Nugrahawan, Ahmad Rizki (Indonesian Institute for Counseling, Education and Theraphy, 2023)
The changing times make technology develop rapidly so that it affects teaching and learning activities. Technologi developments can be used to support the ease of learning. One of them is the barusida application, this application contains material on nahwu, sharaf and mufradat. The existence of the application is expected to provide an improvement in Arabic learning outcomes. This study used a quantitative approach with experimental research techniques with a one-group pretest-posttest design model. The analysis techniques used are simple regression analysis, correlation coefficient, determination coefficient and t-test hypothesis test with a significance level of 5%. The population used in this study were 7th grade students of SMP Muhammadiyah 6 Jakarta with purposive sampling techniques. Based on the results of this study, it can be seen that every increase in the use of the BARUSIDA application, there will be an improvement in learning outcomes of 0.796; and has a high relationship with r = 0.511; also had an influence of 26.1% on the improvement of Arabic language learning; With a tcount of 3.146 and a ttable of 2.042, it means this tcount > ttable. So H1 is accepted, which means that the BARUSIDA application is effective in improving Arabic learning outcomes of 7th grade students of SMP Muhammadiyah 6 Jakarta. So it can be concluded that the BARUSIDA application is effective as a learning medium which is significantly improve the Arabic learning outcomes of 7th grade students of SMP Muhammadiyah 6 Jakarta.